New insights on the taxonomy and phylogenetic relationships of the Neotropical genus Phoebis (Pieridae: Coliadinae) revealed by molecular and morphological data - Murillo-Ramos, Leidys; Torres, Renzo Hernández; Águila, Rayner Núñez; Ayazo, Roger (Zootaxa, 2018)
Phoebis Hübner (1819) is a genus of the Neotropical subfamily Coliadinae (Lepidoptera: Pieridae). The highest diversity is found in the Greater Antilles islands in the Caribbean region. Although from the taxonomic point of view, Phoebis seems to be a stable genus, there is no phylogenetic hypothesis corroborating the monophyly of the genus. In this study, we used both morphological characters and a genetic dataset consisting of one mitochondrial (COI) and three nuclear markers (RpS5, MDH, Wingless). The matrix was concatenated and analysed with parsimony under implied weights (IW). Also, the concatenated data set was analysed using maximum likelihood and Bayesian inference evolutionary methods, and ancestral states reconstruction with characters traditionally used for classification of Phoebis was carried out. The same topology was recovered by Parsimony, ML and BI analysis, and suggest that Phoebis is not a monophyletic genus, with Aphrissa and Rhabdodryas nested within it. Our findings allow us to consider the genera Rhabdodryas syn.rev. and Aphrissa syn.rev. to be synonyms of Phoebis. These results have implications for the systematics of Phoebis and the genera that should be accepted in Coliadinae.